Semangat Otonomi dan Kebutuhan Daerah: Kajian terhadap Penyempurnaan UU Nomor 22 Tahun 2009 - Kurniawan Kurniawan (Universitas Syiah Kuala, 2010)
ABSTRACT: This article aim is to describe any considerations that form the background done amendment toward the act Number 22 of 1999 and explains regarding the development current authonomy concept and its relation to the dynamic of regional people needs, especially under the act Number 32 of 2004. Through the study shows that the main consideration promulgating the act Number 22 of 1999 is caused many changes in social, and political aspect in the community life, beside that the present of this act also as an effort in responding regional area needs. It occured caused available independent and innovation challenge under impleneted decentralization in regions area. Beside the impact emerged in the act Number 22 of 1999 aplication as the background enacted revision toward this act, the revision challenge to this act emerged in the global perspective caused strategic, in which the economic globalisation and free trade which challenge competitive efisiency of the regional people. Therfore, the changes stipulation of the autonomy issue from day to day as stated above is concreat evidence that exist the dynamic of regional people needs move away routinely. This fact must be noted by the law maker and other related stakeholders so that in law making process must be sensitive and carefull in overseeing the dynamics. For the future, Expected, every single law level in relation to autonomy issue can adapting with the regional people needs and globalization factor. Autonomy Spirit and Regional Needs